A Comfortable Palatal Delayed Surgical Obturator for Hemimaxillectomy Patients - Paudel, SP; Paudel, S.; Dhungana, M.; Shrestha, P. (Journal of Nepalese Prosthodontic Society, 2018)
A surgical obturator prosthesis is commonly used as an effective means for rehabilitating patient with hemi-maxillectomy defect. The obturator supports the soft tissues after surgery and minimizes the contraction of scar and disfigurement thereby making a positive effect on patient’s overall function and psychology. The goal of prosthodontics to restore missing orofacial structures for improving facial esthetics and oral function for such patients. The inability to achieve adequate retention, stability, support and comfort due to the friability of healing tissues are the common problems associated with prosthetic treatment in the initial phase of treatment. This case report demonstrates a simple technique to overcome such difficulties by the use of soft lining materials in the delayed surgical obturator.